LEGAL EDUCATION IN RUSSIA: HISTORY, PROBLEMS AND PROSPECTS - Dmitry A. Sumskoy (Вестник Северо-Кавказского федерального университета, 2022)
The article analyzes the retrospective and current state of legal education in Russia, describes the problems faced by the Universities involved in the training of lawyers. The author makes proposals for the reform of legal education.